Factors in the Use of Workplace Health Promotion on Back Health. Results of the Survey “German Health Update” - Hermann, Sophie; Starker, Anne; Geene, Raimund; Jordan, Susanne (Frontiers in Public Health, 2021)
Backround: The influence of the working environment on the back health of employees is well documented. Many companies have begun to offer employees access to services to promote back health. Factors affecting the use of these offers at the population level have received little investigation to date. The current study examined the socio-demographic factors, physical activity and health-related factors, and work-related factors associated with the use of offers of workplace health promotion for back health in Germany. Materials and Methods: In the representative population-based cross-sectional study “Gesundheit in Deutschland aktuell” (GEDA 2014/2015-EHIS) conducted by the Robert Koch Institute, 12,072 employees aged 18 to 64 years old were surveyed from November 2014 to July 2015 regarding the use of back health services in their companies. In addition to socio-demographic factors, the survey examined working hours, physical activity in leisure time, health awareness and subjective complaints in the lower back or other chronic back problems in the last 12 months. The interaction of these factors with the utilization of back health services was tested using multiple logistic regression models. Results: Women used back health services more often than men (women: 25.5%; men: 18.1%). Female gender was associated with part-time employment (OR 0.72) and a strong to very strong level of health awareness (OR 1.40). Male gender was associated with age between 30–44 years (OR 1.99) and 45–64 years (OR 2.02), low socioeconomic status (OR 0.48), endurance activity of less than 2.5 hours per week (OR 0.62), and absence of lower back pain or other chronic back conditions for the last 12 months (OR 0.48). Conclusion: The present study is the first to provide findings regarding the factors associated with the utilization of company offers to promote back health at the population level, and from the perspective of employees in Germany. The results revealed that the relevant factors for participating in offers differ for women and men. To reach more employees, workplace health promotion offers for back health should be designed specifically for each individual, considering gender and age, working hours, health awareness and behavior, and health state.